Improving Medical School Education on the Care of Sexual Assault Patients: A Quasi-Randomized Controlled Study - Hoopes, Katherine; Lewitt, Tessa; Naseem, Anum; Messman, Anne; Kouyoumjian, Sarkis (International Journal of Medical Students, 2021)
Introduction: Comprehensive healthcare for survivors of sexual violence is essential to prevent the diverse sequelae associated with the assault. In partnership with a local rape crisis center, we designed an educational module with the goal of training medical students on the basic needs of sexual assault patients with the aim to see if there was a significant difference in preparedness to counsel such patients. Methods: This quantitative quasi-randomized controlled study tested the effectiveness of an educational module on improving medical student preparedness for encounters with victims of sexual assault. A one-hour presentation, focusing on basic medical and legal knowledge regarding sexual abuse and compassionate patient-centered care, was provided to the intervention group during their compulsory Year 4 Emergency Medicine clerkship orientation. At the end of the month, students in the intervention and control groups were assessed using a standardized patient encounter simulating the presentation of a victim of sexual assault. Scores were determined by standardized patients, who utilized two checklists-one widely used for communication skills (KEECC-A) and the other focusing on sexual assault (WC-SAFE-specific). Results: For the KEECC-A, there was no significant difference in scores between the control and intervention groups (p=0.9257, 95% Confidence Interval [95%CI] 14.42,15.58]). The WC-SAFE-specific checklists were significantly different between the intervention and control groups (p=0.0076, 95%CI 3.79,4.21). Conclusion: Our sexual assault module increased preparedness of medical students for encounters with sexual assault victims and provide trauma-informed care.